2017
DOI: 10.1186/s13014-017-0836-6
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score-matching analysis of postoperative radiotherapy for stage IIIA-N2 non-small cell lung cancer using the Surveillance, Epidemiology, and End Results database

Abstract: BackgroundTo investigate the effects of postoperative radiotherapy (PORT) on the survival of patients with resected stage IIIA-N2 non-small cell lung cancer (NSCLC).MethodsA total of 3,334 patients with resected stage IIIA-N2 NSCLC in 2004 to 2013 were identified in the Surveillance, Epidemiology, and End Results database and stratified according to use of PORT. Propensity score-matching (PSM) methods were used to balance the baseline characteristics of patients who did (n = 744) or did not (n = 744) undergo P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…The prognostic value of tumor size and pT stage in pIIIA-N2 NSCLC has also been investigated in some studies 36-38; the results indicated that tumor size and pT stage might be prognostic indicators for survival. A few studies tried to assess the efficacy of PORT according to the pT stage or tumor size, but yielded conflicting results 12, 15, 16, 22. The present meta-analysis showed no significant differences in OS between the PORT and non-PORT groups for either patients with tumor >3.0 cm or pT2-3 tumor or those with tumor 3.0 cm or less or pT1 tumor.…”
Section: Discussioncontrasting
confidence: 57%
“…The prognostic value of tumor size and pT stage in pIIIA-N2 NSCLC has also been investigated in some studies 36-38; the results indicated that tumor size and pT stage might be prognostic indicators for survival. A few studies tried to assess the efficacy of PORT according to the pT stage or tumor size, but yielded conflicting results 12, 15, 16, 22. The present meta-analysis showed no significant differences in OS between the PORT and non-PORT groups for either patients with tumor >3.0 cm or pT2-3 tumor or those with tumor 3.0 cm or less or pT1 tumor.…”
Section: Discussioncontrasting
confidence: 57%
“…Also, the SEER database contains no information about chemoradiotherapy, metastatic LN stations, and some other factors that can influence the results from PORT. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study found that pN 2 patients treated with postoperative chemotherapy combined with sequential PORT could obtain a longer median survival time (47.4 months Vs. 23.8 months) and a higher 5-year survival rate (47.4% Vs. 34.0%) than postoperative chemotherapy alone. After this, many large retrospective studies based on the SEER database or NCDB database showed that PORT could greatly reduce the risk of death in patients with IIIA N 2 resectable NSCLC [7,16]. A small sample prospective randomized controlled study published in 2014 compared the effect of postoperative adjuvant chemoradiotherapy (POCRT) and postoperative adjuvant chemotherapy (POCT) in patients with pIIIA N 2 [17].…”
Section: Discussionmentioning
confidence: 99%